Application of ultrasound‐assisted enzymatic extraction to enhance triterpenoid content and the biological properties of Vietnamese Ganoderma lucidum extract. Issue 7 (25th May 2022) - Do Dat, Tran; Chuong, Nguyen Phan Thi Cam; Anh, Nguyen Minh; Viet, Nguyen Duc; Thanh, Vuong Hoai; Long, Nguyen Huynh Bach Son; Oanh, Huynh Ngoc; Nam, Hoang Minh; Phong, Mai Thanh; Hieu, Nguyen Huu
Abstract: The ultrasound‐assisted enzymatic extraction (UAEE) in this work was utilized to extract triterpenoid from Ganoderma lucidum ( G. lucidum ). The enzyme concentration (%), ethanol: material ratio (ml/g), ultrasonic duration (min), ultrasonic temperature (°C), and ultrasonic power (W) were all studied as factors impacting triterpenoid content. The experiment was developed using the Plackett–Burman model to filter out the influencing factors and choose the component that has the greatest impact on the triterpenoid content in order to improve the extraction conditions using the Box–Benhken model. The result showed that the highest triterpenoid content of 11.65 mg/g could be obtained under extraction conditions including enzyme concentration of 2.5%, ethanol:material ratio of 20:1 ml/g, and ultrasonic power of 480 W. The results of gas chromatography–mass spectrometry and Fourier‐transform infrared spectrometry analysis showed the presence of more phytochemicals in the extract obtained using UAEE compared with the maceration method. Scanning electron microscopy images were used to confirm the assistance of enzymes and ultrasound waves to disrupt the cell walls of G. lucidum . The antibacterial property of the extract by UAEE was evaluated against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa and Salmonella enterica and able to suppress the development of hepatocellular carcinoma, breast carcinoma, and epidermic carcinoma. Practical applications: The main objective of this paper is to improve extraction efficiency of triterpenoid from Ganoderma lucidum with the combination of enzymatic‐assisted extraction and ultrasound‐assisted extraction. Even though many researchers were worked on different extraction techniques, very few researchers were reported the factor‐screening experiment using Plackett–Burman model and optimization of this extraction system using Box–Behnken model. The anticancer activity of the extract is the main criteria for evaluating the quality of this product. The results found that enzyme concentration, ethanol: material ratio, and ultrasonic power had a significant impact on triterpenoid content, and the extract under optimum conditions exhibited potential medium anticancer capacity using MTT assay. This result is especially useful in applying G. lucidum extract in various fields including health promotion, functional food, and cancer therapy.